Happiness, sleep quality, and self-care ability among community-dwelling older adults in Tehran, 2023 - Milad Bakhtiyary; Farshad Sharifi; Keyvan Karimi; Mohammad Salehpoor-Emran; Fatemeh Sadat Mirzadeh; Pouya Farokhnezhad Afshar (BMC Geriatrics)
Abstract Background Population aging presents a significant challenge that requires comprehensive planning. Limited research has been done on the interconnections between happiness, sleep, and self-care in older adults. This study aimed to determine the Happiness, Sleep quality, and Self-care ability among community-dwelling older adults in Tehran, 2023. Methods This is a cross-sectional study. We selected 306 eligible, community-dwelling older adults through multistage sampling. Participants were recruited from comprehensive health service centers. We employed three assessments: the Oxford Happiness Inventory (OHI), the Pittsburgh Sleep Quality Index (PSQI), and the Self-Care Ability Scale for the Elderly (SASE). Data analysis was conducted using SPSS version 27, the Spearman correlation test, and univariate and multivariate linear regression analyses. Results The results indicated that 58% of older adults were male, 67.6% were married, and 44% were retired. A multivariate linear regression analysis revealed a significant association with happiness. Self-care ability had a negative impact (β = -1.50, p < 0.001), while sleep quality had a positive effect (β = 0.50, p < 0.001). Conclusion Self-care and sleep quality are associated with overall happiness. Policymakers and planners should prioritize happiness enhancement by addressing its relationship with sleep and self-care practices.